BURNOUT AKADEMIK PADA SISWA SMP NEGERI 7 PADANG - Rohila; Zadrian Ardi; Nurfarhanah; Frischa Meivilona Yendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Academic burnout is a psychological phenomenon that has increasingly gained attention in recent years. It refers to a state in which individuals experience exhaustion both mentally and physically as a result of prolonged academic demands. This study aims to describe the level of academic burnout among students facing high academic workloads, specifically focusing on students of SMP Negeri 7 Padang. The research employed a quantitative approach using a descriptive research design. The sample consisted of 77 students, including 35 males and 42 females, all of whom participated in academic enrichment programs. The sampling technique used was purposive sampling, and the data were analyzed using descriptive statistical analysis. The findings revealed that the overall level of academic burnout among students at SMP Negeri 7 Padang was categorized as low (44.15%). This indicates that students were generally able to adapt to academic demands without experiencing significant levels of academic exhaustion. In general, the students demonstrated healthy psychological conditions, good learning motivation, and sufficient self-confidence in their academic abilities.